Exposure of young rats to high estrogen doses leads to degeneration of elongated spermatids - Pinto, M. E.; Vilamaior, P. S. L.; Taboga, S. R. [UNESP]; Goes, R. M. [UNESP] (Churchill Livingstone, 2008)
Single high doses of estrogen (35 mg/kg body weight) were administered to young rats aiming to exacerbate its effects on germ cell populations. The short-term (1 week) and medium-term (7 weeks) consequences of this estrogenic treatment (ET) on the testis were evaluated using light and electron microscopies, quantitative methods and TUNEL reaction. Short-term ET led to 50% atrophy of the testis, however, in the medium term the gonado-somatic index was recovered. No histopathological alterations were found at seminiferous epithelium except for short-term severe degeneration of elongated spermatids (EL) and low frequency of these cells in both time intervals. Two morphologically distinct patterns of degeneration were observed: (1) clusters of EL which were TUNEL-negative and exhibited bizarre appearance and nuclear fragmentation, (2) isolated apoptotic EL within the cytoplasm of Sertoli cells (SC). Both degenerative phenomena were more frequent in stages III - VIII of seminiferous cycle, whereas at stages I and II only coiling of flagellum was observed. One week after ET, small amounts of EL were detected in stages IX - XII, suggesting spermiation failure. Signs of functional SC damage such as an accumulation of myelin-like inclusions in their cytoplasm were observed in the short but not medium-term. However, the apoptotic rates still remained five times higher and the number of elongated spermatids was three-fold lower. Our data indicate that exposure to a high dose of estrogen around puberty has stage-specific effects on the testis and causes massive degeneration of elongated spermatids. (c) 2007 Elsevier Ltd. All rights reserved.
Keywords: testis; Estrogen; Spermatogenesis; Apoptosis; Rat